Pengaruh Return On Assets Dan BOPO Terhadap Market Share Pada Bank Syariah - Maulana, Adam; Ariffin, Muhammad; Gendalasari, Gen Gen (Jurnal Ilmiah Manajemen Kesatuan, 2021)
This study aims to determine the extent of the influence of Return On Assets (ROA) and Operational Costs on Operational Income (BOPO) on Market Share in Islamic Banks in Indonesia as measured using Third Party Funds. This research was conducted using company publication reports from the first quarter or March 2014 to the fourth quarter or December 2018 for five years, namely the 2014-2018 period from Bank Syariah Mandiri, Bank Muamalat Indonesia, Bank BRI Syariah, Bank BNI Syariah, and Bank Mega. Sharia. The statistical method used is panel data regression, with t test and f test. The t test is used to test the effect of the independent variable partially on the dependent variable. The f test is used to test the effect of the independent variables together on the dependent variable using the EViews9 system. It can be seen from the results that have been partially tested that BOPO has a significant effect on Market Share because it has a significance value <0.05 (0.0005). Then for ROA does not have a significant effect on Market Share because it has a significance value> 0.05 (0.0546). Simultaneously, the BOPO and ROA variables both have a significant effect on Market Share with a significance value <0.05 (0.000000). The predictive ability of these two variables on Market Share is 72.75% as shown by the amount of adjusted R2, while the remaining 27.25% is influenced by other factors that are not included in the research model. Keywords : Return On Assets (ROA), Operational Costs on Operational Income (BOPO), and Market Share.